The Impact of Workforce Aging on European Productivity - Aiyar, Shekhar (IMF Working Papers; Working Paper ;, 2016)
The age-distribution of Europe's workforce has shifted towards older workers over the past few decades, a process expected to accelerate in the years ahead.. This paper studies the effect of the aging of the workforce on labor productivity, identifies the main transmission channels, and examines what policies might mitigate the effects of aging. We find that workforce aging reduces growth in labor productivity, mainly through its negative effect on TFP growth. Projected workforce aging could reduce TFP growth by an average of 0.2 percentage points every year over the next two decades. A variety of policies could ameliorate this effect.